The Inside and Outside Revenue Impact of Regional Gambling Taxes in Spain. (12th December 2013) - Leal, Andrés; López‐Laborda, Julio; Rodrigo, Fernando
Abstract Using panel data methods, for all the Spanish Autonomous Communities and for the period 1999–2009, the present study estimates the revenue of the casinos in each Autonomous Community on the basis of four variables of interest related to the taxation of gambling in each Community, the taxation in the neighboring Autonomous Communities and the expansion of online gambling, and certain economic and sociodemographic control variables. The estimation performed permits the verification of the hypotheses that the taxation of gaming in a region and the expansion of online gambling negatively affect the revenue accrued by the casinos located in that region, but does not offer evidence that the effect produced by the differences in taxation among neighboring regions is significant. The results obtained also confirm the expected impact on the casinos' revenue of the existence of "type" gamblers (young males, and tourists) and of the economic situation (income and unemployment).